PENGEMBANGAN MEDIA PEMBELAJARAN ASTERIA BERBANTU AUGMENTED REALTY PADA MATERI TATA SURYA TERHADAP KETERAMPILAN PROSES SAINS IPAS - Aprilia Saemah, aprilia saemah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of technology in 21st century education is increasingly needed to meet the needs of the learning process. This study aims to identify the need for asteria development as a technology-based media in learning solar system material in grade V of Elementary School. This study uses a quantitative method with a research population consisting of teachers and students of grade V of SDN Panjalin Lor I. The research sample involved 10 teachers and 33 students selected through purposive sampling techniques to ensure proper representation of the target population. Data collection was carried out by conducting a media needs questionnaire, interviews, and observations. The results of the study showed that teachers and students agreed on the importance of developing asteria learning media assisted by assemblr edu to facilitate more interesting and effective learning. Most teachers find it difficult to use technology-based media and find it difficult to convey solar system material abstractly. Students experience obstacles in understanding the material due to the limitations of existing learning media. This study confirms that the need to develop asteria learning media assisted by assemblr edu is based on the need to develop asteria media to make the learning process more interesting, interactive, by adding visualization elements that can help students understand abstract concepts.